PELAKSANAAN PEMBELAJARAN MENJAHIT LEVEL SATU PADA LEMBAGA KURSUS DAN PELATIHAN (LKP) - Kumala Dewi; Agus Zainal Ramat; Ririn Gusti (UNIB Press, Universitas Bengkulu, 2019)
The objectives of this study were: (1) The purpose of this stady was to determine the learning objectives of sewing courses at level one in the Mayang Sari course Institusi in Bengkulu City (2) Knowing the source of learning sewing courses at level one at the Mayang Sari training institusi and city of Bengkulu (3) Knowing the sewing course learning strategy at level one at the Mayang Sari Course and training institute in Bengkulu City (4) Know the learning media for sewing courses at level one at the Mayang Sari course and training institusi in Bengkulu (5) Know the evaluation of learning sewing courses at level one in the Mayang Sari training course institute in Bengkulu. The research method used is a qualitative method with a descriptive approach participants in the research were Ibu Sorehalela as the chairperson of the Mayang Sari training curriculum. Data collection techniques used were non-participant observation, structured, interviews, and documentation. To test the validity and reliability of the data using triangulation of sources, techniques and time. Based on the analysis that has been done that the management of sewing courses at the Mayang Sari training institute and courses in the city of Bengkulu. (1) The goal of the sewing course is to improve the personal and social qualities of each individual learning, to provide a sense of security and comfort while learning to sew(2) learning resources at LKP mayang sari are assence of digital media, guidebooks and references from fellow sew (3) the sewing course learning strategies for LKP mayang are essentially giving the theory first to practice while the method used is discourse, discussion, practice and simulation methods (4) the media that we use for sewing classes in LKP mayang is essentially the set of them one computer, printer one unit,laptop 1 unit LCD 1 unit and has the means and infrastructure of a course room, office building, sewing machine and machine, (5) the evaluation for the sewing course is done with the written exam and the practice exam of participants learning to sew. Keywords: Implementation of the sewing course